Photosynthesis regulation during leaf ontogeny progenies of Hevea brasiliensis and Hevea pauciflora grown under two water conditions - Pita, Francisco Antonio Oliveira; Cano, Marco Antonio Oliva; Lopes, Nei Fernandes (Pesquisa Agropecuaria Brasileira, 2014)
Chlorophyll synthesis, stomatal behaviour and CO2 balance were studied during the period of leaf ontogeny in seedlings of H. brasiliensis (lAN 873) and H. pauciflora grown under two water conditions. When submitted to a water stress H. pauciflora was able to maintain higher and more stable water potentials (Ψw) than other species. Reduction in photosynthesis rates in water stressed plants was associated to a drop in Ψw in both species. This reduction in H. brasiliensis was related to a decreasing 50% in chlorophyll synthesis and an increase in stomatal resistance. Under water stress H. pauciflora showed only an enhancement in the rates of photorespiration.